EFFEK SAMPING PENGGUNAAN PONSEL - Enny, Enny (Gema Teknologi, 2014)
Enny, in this paper explain that many mobile phone users around the us, but only a portion of the concerned about the dangers of cell phones. This paper was compiled to determine the impact and solutions of cell phone radiation. Mobile phones emit electromagnetic waves which will affect the surrounding environment. Based on existing information, cell phone radiation is thought to cause cancer. Waves emitted from mobile phones over the air is causing electromagnetic radiation. Potential disrubtion of health consequences of radiation electromagnetic field has become an issue which examined till now, so found a variety of health disorders as a result of mobile phone users that includes the impact of mild and severe impact. Experts have discovered some efforts to minimize the effects of cell phone radiation on health of mobile phone users. Every user should know the dangers of mobile phone users. Radiation caused cell phone not only arise when used, but when putting a cell phone in your Pocket can also be exposed to any radiation. Therefore, mobile users need to know how to use a cell phone. Users should pay attention to the level of radiation caused by cell phones, so that the influence of electromagnetic radiation on health can be scaled down for mobile users. Keywords: side effects of cell phone use